10-minute makeup : 50 step-by-step looks from fresh and natural to catwalk chic - Entrup, Boris, 1978- (Nee York: Dorling Kindersley, 2014)
Offers step-by-step, illustrated instructions for fifty versatile looks that can be created in only ten minutes, including detailed information on basic techniques, products, equipment, and special makeup tips and tricks. --Publisher's description.
Basics. Skincare ; Brushes and tools ; Products -- 50 looks -- Basic techniques. Foundation ; Concealer ; Blush ; Face types ; Eyes ; Pencil eyeliner ; Eyelashes ; Liquid eyeliner ; Lips ; Smoky eyes ; Eyebrows -- Beauty tips for every age -- S.O.S. tips.
Translated from the German.
Keywords: Artet boterore; Arti vizual-kozmetika; Artiste boterore; Beauty, Personal. -- Kujdesi personal; Cosmetics. -- Kozmetika; Women -- Health and hygiene-shendeti dhe higjena; Beauty, Personal; Cosmetics; Women -- Health and hygiene; Make-up-grimi; Grimi-kujdesi personal-teknika -mjetet- moda-fashion; Mjetet -grimi-mascara-korrektuesi-fondatina-buzekuq-pudra-lapsi i syve